Economic diversity of farming systems and possibilities for structural adjustment in mountain livestock farms - Manrique E.; Olaizola A.; Bernués A.; Maza M.T.; Sáez A. (Systèmes d'élevage et gestion de l'espace en montagnes et collines méditerranéennes, 1999)
Livestock farming systems have been studied in Spanish less favoured mountainous areas. Farming activities require an adequate return to labour and also public subsidy policies if the new environmental functions assigned to these areas under CAP are to be fulfilled. Under an hypothetical scenario of zero subsidy, the great diversity among farms would produce different responses. A sample of livestock farms of a representative Pyrenean area was typified from the point of view of the economic and structural characteristics, using multivariate statistical methods (principal component analysis and cluster analysis). Relationships between herd size, performance and labour productivity are particularly noticeable. Productive orientation of farms is the variable that most differentiated the types obtained. Large cattle farms obtained the highest outputs of farming activities, whereas non-transhumant sheep farms obtained the lowest. Under the current subsidy conditions, all types of farms were profitable. Nevertheless, when subsidies are not taken into account, 38 per cent of sample farms obtained negative economic results, especially transhumant sheep farms and mixed sheep-cattle farms. Cattle farms obtained better economic results.